Cooperatives and its effect on society - Alejandro Martínez Charterina (AECOOP Escuela de Estudios Cooperativos, 2015)
The Blueprint for a cooperative decade of the International Cooperative Alliance, approved after celebrating the United Nations International Year of Cooperatives, places special emphasis on the cooperative business model. This is being particularly suitable to face the current crisis regarding participation in business ownership and decision-making (democratic management), the search for economic, social and environmental sustainability, and the existence of an identity consisting of cooperative values and principles. The cooperative model focuses on individuals and the society in which they perform their activities.